2023
DOI: 10.1128/spectrum.02424-22
|View full text |Cite
|
Sign up to set email alerts
|

Description of Gut Mycobiota Composition and Diversity of Caprinae Animals

Abstract: In this study, we elucidated and analyzed the structure of the gut mycobiota of Caprinae animals from different regions. This study revealed differences in the structure of the gut mycobiota among Caprinae animals from different geographical environments. Based on previous findings, correlations between fungal and bacterial communities were analyzed. This study adds to previous research that has expanded the present understanding of the gut microbiome of Caprinae animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…The results obtained regarding the taxonomy of fungi in alpacas (Figure 4A) show a high degree of concordance with previous studies on ruminants [56][57][58][59][60][61]. Various studies have identified Ascomycota and Basidiomycota as the most predominant fungal phyla in mammals and ruminants, as seen in cows [56][57][58], buffaloes [59], and goats [60,61]. Similarly, the classes identified in alpaca protists in our study (Figure 4B) have been reported in previous research on mammals, including humans [43,50], pandas [48], primates [49], and cows [57].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results obtained regarding the taxonomy of fungi in alpacas (Figure 4A) show a high degree of concordance with previous studies on ruminants [56][57][58][59][60][61]. Various studies have identified Ascomycota and Basidiomycota as the most predominant fungal phyla in mammals and ruminants, as seen in cows [56][57][58], buffaloes [59], and goats [60,61]. Similarly, the classes identified in alpaca protists in our study (Figure 4B) have been reported in previous research on mammals, including humans [43,50], pandas [48], primates [49], and cows [57].…”
Section: Discussionsupporting
confidence: 89%
“…The results obtained regarding the taxonomy of fungi in alpacas (Figure 4A) show a high degree of concordance with previous studies on ruminants [56][57][58][59][60][61]. Various studies have identified Ascomycota and Basidiomycota as the most predominant fungal phyla in mammals and ruminants, as seen in cows [56][57][58], buffaloes [59], and goats [60,61].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The intestinal microbiota of cattle includes diverse fungal and protist communities. The dominant fungal phyla in cattle gut microbiota are Ascomycota, Basidiomycota, and Neocallimastigomycota [13]. These fungal phyla play crucial roles in various gut functions [14].…”
Section: Introductionmentioning
confidence: 99%